Treatment of Maxillary Midline Diastema Using Removable Clear Trays and Elastics: A Case Report - BEYCAN, KADİR (GALENOS YAYINCILIK, 2017)
Maxillary midline diastema is a common esthetic problem requiring treatment. This case presentation shows the treatment of a patient with a minor midline diastema using removable clear trays and elastics. A 20-year-old female patient, whose chief complaint was a small diastema between upper central incisors, had a symmetric face and competent lips. Intraoral examination showed class 1 buccal segments relationship with normal overjet and overbite. For the closure of midline diastema, an upper clear tray was fabricated and it was sectioned at the mesial third of each central incisor to create separate left and right trays with attachments for the elastic wear. Two months later, maxillary midline diastema was totally closed and a bonded maxillary 3-3 retainer was placed for retention. The esthetic problem was resolved. Clear appliance is aesthetic, and sufficient to close maxillary midline diastema.
Keywords: Maxillary midline diastema; class 1 malocclusion; clear tray; ORTHODONTIC CORRECTION; FOLLOW-UP; RELAPSE; TEETH